Three-Dimensional Printable Magnetic Hydrogels with Adjustable Stiffness and Adhesion for Magnetic Actuation and Magnetic Hyperthermia Applications - Xueting Xuan; Yi Li; Xing Xu; Zhouyi Pan; Yu Li; Yonghao Luo; Li Sun (Gels)
Stimuli-responsive hydrogels hold immense promise for biomedical applications, but conventional gelation processes often struggle to achieve the precision and complexity required for advanced functionalities such as soft robotics, targeted drug delivery, and tissue engineering. This study introduces a class of 3D-printable magnetic hydrogels with tunable stiffness, adhesion, and magnetic responsiveness, prepared through a simple and efficient “one-pot” method. This approach enables precise control over the hydrogel’s mechanical properties, with an elastic modulus ranging from 43 kPa to 277 kPa, tensile strength from 93 kPa to 421 kPa, and toughness from 243 kJ/m3 to 1400 kJ/m3, achieved by modulating the concentrations of acrylamide (AM) and Fe3O4 nanoparticles. These hydrogels exhibit rapid heating under an alternating magnetic field, reaching 44.4 °C within 600 s at 15 wt%, demonstrating the potential for use in mild magnetic hyperthermia. Furthermore, the integration of Fe3O4 nanoparticles and nanoclay into the AM precursor optimizes the rheological properties and ensures high printability, enabling the fabrication of complex, high-fidelity structures through extrusion-based 3D printing. Compared to existing magnetic hydrogels, our 3D-printable platform uniquely combines adjustable mechanical properties, strong adhesion, and multifunctionality, offering enhanced capabilities for use in magnetic actuation and hyperthermia in biomedical applications. This advancement marks a significant step toward the scalable production of next-generation intelligent hydrogels for precision medicine and bioengineering.